Quantitative disease progression model of α‐1 proteinase inhibitor therapy on computed tomography lung density in patients with α‐1 antitrypsin deficiency. (11th August 2017) - Tortorici, Michael A.; Rogers, James A.; Vit, Oliver; Bexon, Martin; Sandhaus, Robert A.; Burdon, Jonathan; Chorostowska‐Wynimko, Joanna; Thompson, Philip; Stocks, James; McElvaney, Noel G.; Chapman, Kenneth R.; Edelman, Jonathan M.
Abstract : Aims: Early‐onset emphysema attributed to α‐1 antitrypsin deficiency (AATD) is frequently overlooked and undertreated. RAPID‐RCT/RAPID‐OLE, the largest clinical trials of purified human α‐1 proteinase inhibitor (A1 ‐PI; 60 mg kg –1 week –1 ) therapy completed to date, demonstrated for the first time that A1 ‐PI is clinically effective in slowing lung tissue loss in AATD. A posthoc pharmacometric analysis was undertaken to further explore dose, exposure and response. Methods: A disease progression model was constructed, utilizing observed A1 ‐PI exposure and lung density decline rates (measured by computed tomography) from RAPID‐RCT/RAPID‐OLE, to predict effects of population variability and higher doses on A1 ‐PI exposure and clinical response. Dose–exposure and exposure–response relationships were characterized using nonlinear and linear mixed effects models, respectively. The dose–exposure model predicts summary exposures and not individual concentration kinetics; covariates included baseline serum A1 ‐PI, forced expiratory volume in 1 s and body weight. The exposure–response model relates A1 ‐PI exposure to lung density decline rate at varying exposure levels. Results: A dose of 60 mg kg –1 week –1 achieved trough serum levels >11 μmol l –1 (putative 'protective threshold') in ≥98% patients. Dose–exposure–response simulations revealed increasing separation between A1 ‐PI and placebo in the proportions of patients achieving higher reductions in lung density decline rate; improvements in decline rates ≥0.5 g l –1 year –1 occurred more often in patients receiving A1 ‐PI: 63 vs. 12%. Conclusion: Weight‐based A1 ‐PI dosing reliably raises serum levels above the 11 μmol l –1 threshold. However, our exposure–response simulations question whether this is the maximal, clinically effective threshold for A1 ‐PI therapy in AATD. The model suggested higher doses of A1 ‐PI would yield greater clinical effects.